a. \(x^2-x-6=0\)
\(\Leftrightarrow\left(x^2+2x\right)-\left(3x+6\right)=0\)
\(\Leftrightarrow x\left(x+2\right)-3\left(x+2\right)=0\)
\(\Leftrightarrow\left(x+2\right)\left(x-3\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=-2\\x=3\end{matrix}\right.\)
b. \(x^2+8x-20=0\)
\(\Leftrightarrow\left(x^2-2x\right)+\left(10x-20\right)=0\)
\(\Leftrightarrow x\left(x-2\right)+10\left(x-2\right)=0\)
\(\Leftrightarrow\left(x-2\right)\left(x+10\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=2\\x=-10\end{matrix}\right.\)
c. \(x^4+4x^2-5=0\)
\(\Leftrightarrow\left(x^4+4x^2+4\right)-9=0\)
\(\Leftrightarrow\left(x^2+2\right)^2-3^2=0\)
\(\Leftrightarrow\left(x^2+2+3\right)\left(x^2+2-3\right)=0\)
\(\Leftrightarrow\left(x^2+5\right)\left(x^2-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x^2=-5\left(vo.nghiem\right)\\x=1\\x=-1\end{matrix}\right.\)
d. \(x^3-19x-30=0\)
\(\Leftrightarrow\left(x^3-5x^2\right)+\left(5x^2-25x\right)+\left(6x-30\right)=0\)
\(\Leftrightarrow x^2\left(x-5\right)+5x\left(x-5\right)+6\left(x-5\right)=0\)
\(\Leftrightarrow\left(x-5\right)\left(x^2+5x+6\right)=0\)
\(\Leftrightarrow\left(x-5\right)\left[\left(x^2+2x\right)+\left(3x+6\right)\right]=0\)
\(\Leftrightarrow\left(x-5\right)\left[x\left(x+2\right)+3\left(x+2\right)\right]=0\)
\(\Leftrightarrow\left(x-5\right)\left(x+2\right)\left(x+3\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=5\\x=-2\\x=-3\end{matrix}\right.\)